2019
DOI: 10.1002/pmrj.12137
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Version of the Modified Dynamic Gait Index in Patients With Neurologic Disorders

Abstract: Background: Gait instability is common in adults with neurologic disorders and the modified Dynamic Gait Index (mDGI) was recently introduced to assess dynamic balance. However, instrumental assessment is needed to provide quantitative measures. Objective: To develop and validate an instrumented version of the mDGI. Design: Cross-sectional study. Setting: Clinical setting. Participants: Thirty adults with neurologic disorders (10 with multiple sclerosis, 10 with Parkinson disease, and 10 with stroke) and 20 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…However, it must be highlighted that some PwMS showing normal ImRomberg and tandem gait tests could present with dynamic balance deficits that can be detected only through more difficult tasks (i.e., walking over/around an obstacle, walking with head rotations, stairway walking, etc. [ 11 , 20 , 35 , 81 , 82 ]) which are usually executed with physiotherapists in rehabilitation gyms. For this reason, it would be important to advise these individuals, especially if sedentary, to carry out regular physical activity, including dynamic balance.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be highlighted that some PwMS showing normal ImRomberg and tandem gait tests could present with dynamic balance deficits that can be detected only through more difficult tasks (i.e., walking over/around an obstacle, walking with head rotations, stairway walking, etc. [ 11 , 20 , 35 , 81 , 82 ]) which are usually executed with physiotherapists in rehabilitation gyms. For this reason, it would be important to advise these individuals, especially if sedentary, to carry out regular physical activity, including dynamic balance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, wearable inertial measurement units (IMUs), including accelerometers, gyroscopes, and magnetometers, represent cost-effective tools to perform objective assessments of walking in pwMS outside movement analysis labs [19,20], and even during free-living and community contexts [21,22]. IMUs have been widely used to analyse different locomotor tasks in pwMS, such as straight-line over ground [17,[23][24][25][26][27] and treadmill walking [28], standing up, walking, turning, and sitting down (e.g., the TUG) [15,29], walking with head turns and over/around obstacles [30,31], walking while texting [32], and stairway walking [33]. During these tests, several parameters have been extracted from IMUs, including spatio-temporal parameters [15,24,27,28,31,32,34], indexes of gait variability and stability [17,23,24,26,31,33], trunk sway metrics [15,23,30,34], and angular variables [15,25,27,34].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, WHHT, as measured by the Fullerton Advanced Balance scale-short version (10), resulted to be the most impaired item (together with turning 360 • ) also in early-stage PwMS (11). Recently, Cattaneo et al (12) found that WHHT is more impaired in PwMS compared to stroke survivors and people with Parkinson's disease, complementing previous results showing more severe static and dynamic balance deficits in PwMS (7,13,14).…”
Section: Introductionmentioning
confidence: 60%
“…Healthy subjects (HS) and NW-PwMS were equipped with three wireless IMUs (MTw, Xsens, The Netherlands) secured on both shanks (above lateral malleoli) and the sternum. The position of the latter IMU was chosen to better describe sway and possible instability of the upper trunk that, based on our clinical experience, seem to occur more frequently during locomotor tasks particularly demanding in terms of dynamic balance [e.g., TUG test (34), walking while turning the head (13), walking around/over obstacles (13), stairway walking (14)], than during straight-line walking. IMU-derived accelerations and angular velocities were recorded at 75 Hz.…”
Section: Instrumented Assessment-whhtmentioning
confidence: 99%